Engineered ATG8‐binding motif‐based selective autophagy to degrade proteins and organelles in planta. Issue 2 (23rd November 2022) - Luo, Na; Shang, Dandan; Tang, Zhiwei; Mai, Jinyan; Huang, Xiao; Tao, Li‐Zhen; Liu, Linchuan; Gao, Caiji; Qian, Yangwen; Xie, Qingjun; Li, Faqiang
Summary: Protein‐targeting technologies represent essential approaches in biological research. Protein knockdown tools developed recently in mammalian cells by exploiting natural degradation mechanisms allow for precise determination of protein function and discovery of degrader‐type drugs. However, no method to directly target endogenous proteins for degradation is currently available in plants. Here, we describe a novel method for targeted protein clearance by engineering an autophagy receptor with a binder to provide target specificity and an ATG8‐binding motif (AIM) to link the targets to nascent autophagosomes, thus harnessing the autophagy machinery for degradation. We demonstrate its specificity and broad potentials by degrading various fluorescence‐tagged proteins, including cytosolic mCherry, the nucleus‐localized bZIP transcription factor TGA5, and the plasma membrane–anchored brassinosteroid receptor BRI1, as well as fluorescence‐coated peroxisomes, using a tobacco‐based transient expression system. Stable expression of AIM‐based autophagy receptors in Arabidopsis further confirms the feasibility of this approach in selective autophagy of endogenous proteins. With its wide substrate scope and its specificity, our concept of engineered AIM‐based selective autophagy could provide a convenient and robust research tool for manipulating endogenous proteins in plants and may open an avenue toward degradation of cytoplasmic components other than proteins in plant research.